Data Access for the Open Access Literature: PLOS's Data Policy. - Theodora Bloom; Emma Ganley; Margaret Winker (PLoS Medicine, 2014)
The new PLOS Data Policy will require all submitting authors to include a data availability statement as of March 1, 2014. Read more about what this means and see the policy itself in this cross-PLOS Editorial from Theo Bloom and colleagues.